1989
DOI: 10.1111/1523-1747.ep12721505
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Wavelength on Cutaneous Pigment Using Pulsed Irradiation.

Abstract: Several reports have been published over the last two decades describing the successful removal of benign cutaneous pigmented lesions such as lentigines, café au lait macules' nevi, nevus of Ota, and lentigo maligna by a variety of lasers such as the excimer (351 nm), argon (488,514 nm), ruby (694 nm), Nd:YAG (1060 nm), and CO2 (10,600 nm). Laser treatment has been applied to lesions with a range of pigment depths from superficial lentigines in the epidermis to the nevus of Ota in the reticular dermis. Widely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0
3

Year Published

1992
1992
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(39 citation statements)
references
References 13 publications
0
36
0
3
Order By: Relevance
“…6,7 However, certain side effects, especially postinflammatory hyperpigmentation (PIH), are common in Asian people after laser therapy. 8 Double-frequency QS Nd:YAG laser with a 532-nm wavelength is appropriate for destructing melanin-containing cells in the epidermis, 9 although its use is associated with higher risk of PIH compared with QSRL and QSAL. 6 Intense pulsed light (IPL) is a noncoherent, broadspectrum light that allows variations in pulse length, mode, delay between pulses, and fluence.…”
mentioning
confidence: 99%
“…6,7 However, certain side effects, especially postinflammatory hyperpigmentation (PIH), are common in Asian people after laser therapy. 8 Double-frequency QS Nd:YAG laser with a 532-nm wavelength is appropriate for destructing melanin-containing cells in the epidermis, 9 although its use is associated with higher risk of PIH compared with QSRL and QSAL. 6 Intense pulsed light (IPL) is a noncoherent, broadspectrum light that allows variations in pulse length, mode, delay between pulses, and fluence.…”
mentioning
confidence: 99%
“…Licht des Rubinlasers dringt relativ tief in die Haut ein und wird besonders von pigmentreichen Strukturen der Epidermis und Dermis -Melanin, Melanosomen, Melanozyten [20,42,54,58,69] und exogen eingebrachten Farbpigmenten -absorbiert. Durch die extrem schnelle Aufheizung der Zielstruktur kommt es zu einer selektiven Zerstö-rung, wobei diese entweder als Folge des extremen Temperaturgradienten innerhalb der Zielstruktur und/oder aufgrund der Schockwelle/Kavitation bei schneller thermaler Expansion entsteht [8,42].…”
Section: Q-switched Ruby Laser · Tattoos · Lentiginesunclassified
“…Eine selektive Wirkung bei vaskulären Veränderungen kann eingeschränkt mit dem Argonlaser und v.a. mit dem blitzlampengepumpten, gepulsten Farbstofflaser (FPDL, "flashlamppumped-pulsed-dye-laser") erreicht werden [69]. Das Licht des gütegeschalteten Rubinlasers (694 nm) dringt relativ tief in die Haut ein und wird selektiv von dunklen Strukturen -Melanin und exogen eingebrachten Pigmenten -absorbiert und ermöglicht somit die Behandlung von kutanen pigmentierten Hautveränderungen und Tätowierungen.…”
unclassified
“…This principle of localizing the energy to specific targets in the laser exposed field relies upon the combination of laser parameters of wavelength, pulse duration, fluence and spotsize. The effect of one of these laser parameters, wavelength, on melanin pigment has previously been reported [3]. In this study, it was demonstrated that of the five (504,590,694,720,760 nm) wavelengths tested, 504 nm appeared most effective and least problematic for selectively eliminating cutaneous pigment [31.…”
Section: Introductionmentioning
confidence: 95%
“…Dermal pigment is abnormal and many etiologies are responsible for its presence. One such cause, which is of significance here, is pigmentary incontinence resulting from laser irradiation [3]. Therefore, of concern when defining "optimal" parameters for selectively destroying the abnormal pigment in cutaneous pigmented lesions is the need to minimize pigmentary incontinence and prevent melanin granules from being deposited in dermal tissues.…”
Section: Introductionmentioning
confidence: 99%